Mudanças Climáticas” e “Aquecimento Global” – Nova Formatação e Paradigma para o Pensamento Contemporâneo? - Felício, Ricardo Augusto (Ciência e Natura, 2014)
This study analyzes the performance of ensemble forecasts of the European Center for Medium-Range Weather Forecasting model (ECMWF) using the linear wave theory in order to check its performance and specific errors. Seasonal forecast composites for the period 1981 – 2002 were used as well as the ECMWF reanalysis (ERA40) for validation. The analysis of the total wavenumber (Ks) fields and some meridional profiles in selected longitudes indicated that the waveguide predicted by the model is similar to the reanalysis but there are some small but important differences, particularly related to the latitudinal displacement of the waveguides which in turn will affect Rossby wave propagation. Through the analysis of the ray tracing technique it is shown that the model is not able to correctly reproduce the atmosphere mean basic state in the seasonal forecast. Depending on the season or the wavelength propagation the remote impact may be very different, once the phase and energy of the wave will be displaced when compared to observations and therefore the possibility of, for instance, the model to predict rain (or no rain) in one specific region can be compromised.